Struktur Komunitas Spesies Katak dan Kodok Anggota Ordo Anura di Taman Nasional Bromo Tengger Semeru, Jawa Timur - Ludhfiyah, Anggun; Bahri, Saiful; Firdausi, Nirmala (MANILKARA: Journal of Bioscience, 2025)
The Bromo Tengger Semeru National Park (BTSNP) area has a very large area (50,276 ha) covering 4 districts in East Java Province, so it is still necessary to conduct research on frog and toad species that are members of the Anura order in order to contribute to adding and completing databases that have been previously documented. The study aims to measure the diversity, uniformity, and dominance of frog and toad species belonging to the Anura order in several areas that are still included in the BTSNP area, namely Senduro Resort, Ireng-ireng Block, and Ranu Darungan. Observations were made using direct observation methods using Visual Encounter Survey (VES) combined with roaming techniques on transect lines. The results showed that 11 species of frogs and toads of the Anura order were found in the 3 research zones. The species diversity index value in Senduro Resort is in the low category (0.598), while in Ireng-ireng and Ranu Darungan Blocks it is in the medium category (1.183 and 1.006). The species evenness index in the 3 research zones showed moderate values (0.863; 0.85; 0.517), the dominance value obtained was in the low category (0.142; 0.027; 0.010). It was concluded that although the diversity index of frog and toad species was moderate in the 2 research zones, as well as the acquisition of species richness values of 11 species of 138 individual frogs and toads, the overall data of this information has meaning in supporting the management and conservation of frog and toad species members of the order Anura in BTSNP.